A Large Oral Melanoma: A Case Report of a Rare but Aggressive Malignancy - Warin, Kritsasith; Klanrit, Poramaporn; Pattanajakr, Nutdanai (European Journal of Dentistry, 2021)
A variety of black-pigmented lesions of the oral cavity can be found, ranging from harmless benign lesions such as melanotic macule, smoker’s melanosis, amalgam/graphite tattoos, and pigmented nevus to a life-threatening oral malignant melanoma. Oral melanoma is a rare and aggressive malignant tumor that originates from melanocytes’ proliferation and accounts for only 0.5% of all oral malignancies. The etiology is unknown. Most oral melanomas are present at the palate and the upper alveolar ridge, whereas occurrences at the buccal mucosa, the lower alveolar ridge, and the lip are rare, with only a few reports in the literature. The diagnosis is confirmed by a biopsy. The prognosis is poor, with a 5-year survival rate of ~20%. In this report, we present a case of large oral melanoma at the right buccal mucosa involving the right lower alveolar ridge and lip commissure, which are relatively unusual locations for oral melanoma. In addition, immunohistochemical markers used for diagnostic, therapeutic, and prognostic decision-making of oral melanoma are also discussed.
Keywords: melanoma; oral cavity; pathology; immunohistochemistry; palliative care